Patients Experience Self-isolation Covid_19 at Home - Rostime Hermayerni Simanullang; Siti Meilan Simbolon; Masta Melati Hutahaean; Laurena Ginting (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Corona Virus - 19 is a worldwide pandemic disease that causes crises, particularly in the field of health. The government implemented a policy of home isolation for patients who do not have comorbid conditions in order to reduce the impact on patients' self-isolation. The goal of this research is to delve deeply into the experiences of covid-19 patients during self-isolation at home. This is a qualitative study that employs a phenomenological design to investigate life events or patient experiences during self-isolation at home. Data was gathered through direct and indirect interviews lasting 50-60 minutes. The purposive sampling technique was used to select 12 participants. Demographic data questionnaires, interview guides, daily notes, and voice recorders are used as data collection tools. Content analysis is used to analyze data. The study's findings revealed six themes, namely: Theme 1. Participants' signs and symptoms prior to the PCR examination; theme 2. Participants' psychological reactions following the PCR examination; theme 3. The emergence of health conditions among participants during self-isolation at home; theme 4. Tools for monitoring participants' health status during self-isolation at home are available; theme 5. Participants' activities and efforts during self-isolation at home, and theme 6. Participants' expectations of the government, health workers, and the community for self-isolation at home. Abstrak: Corona Virus-19 merupakan penyakit pandemic yang dialami oleh seluruh dunia dan menyebabkan krisis diberbagai dunia terutama di bidang kesehatan. Pemerintah membuat kebijakan isolasi di rumah untuk pasien yang tidak mengalami komorbid sehingga berdampak kepada pasien isolasi mandiri. Tujuan penelitian ini untuk menggali  secara mendalam pengalaman pasien covid-19 selama isolasi mandiri di rumah. Penilitian ini adalah penelitian kualitatif dengan menggunakan desain fenomenologi untuk menggali kejadian hidup atau pengalaman pasien selama isolasi mandiri di rumah. Metode pengumpulan data dengan wawancara medalam secara langsung dan tidak langsung dengan durasi 50-60 menit. Partisipan sejumlah 12 partisipan yang diambil dengan tekhnik purposive sampling. Alat pengumpul data berupa kuisioner data demografi, panduan wawancara, catatan lapangan dan perekam suara. Analisis data dengan menggunakan thematic analysis. Hasil penelitian ditemukan 6 tema yaitu:Tema 1. Tanda   dan Gejala yang dialami Partisipan sebelum dilakukan Pemeriksaan PCR; Tema 2. Dampak psikologis yang dialami Partisipan setelah dilakukan Pemeriksaan PCR; Tema 3. Perkembangan kondisi kesehatan yang dialami Partisipan selama Menjalani Isolasi Mandiri di Rumah; Tema 4. Ketersediaan Alat-Alat untuk Memantau Status Kesehatan Partisipan selama Menjalani Siolasi Mandiri di Rumah; Tema 5. Aktivitas dan Usaha yang dilakukan Partisipan selama Menjalani Isolasi Mandiri di Rumah, dan Tema 6. Harapan Partisipan yang Menjalani Isolasi Mandiri di Rumah terhadap Pemerintah, Petugas Kesehatan dan Masyarakat.